Pendampingan Pengelolaan Home Industry Ikan Asap untuk Meningkatkan Pendapatan Ekonomi Nelayanan di Desa Palang Kabupaten Tuban - Prameswara, Nugraha Ilma; Nusantara, Widya (J+PLUS UNESA, 2023)
Mentoring is an activity carried out by someone for the people around them to become better people. Mentoring can also be said to be a transfer of knowledge carried out by a mentor to people who need assistance. The assistance provided in this Home industry is related to the management of smoked fish production, which requires good management. Smoked fish management carried out in the smoked fish Home industry is (1) planning, (2) implementation and (3) evaluation. The method used in this research is descriptive qualitative. The research location is in Palang Village, Tuban Regency. Data collected used in-depth interview techniques, participant observation and documentation. Data analysis in this research involves data reduction, data display and verification and conclusions. After this stage, the data is tested for validity using credibility, dependability, confirmability and transferability. The results of the research show (1) the process of assisting the management of the smoked fish Home industry uses management which includes planning, implementation and evaluation so that the mentoring process runs well, (2) the obstacles that exist in the process of assisting the management of smoked fish are the existence of natural factors that can hinder production process.